Writing essentials: raising expectations and results while simplifying teaching - Routman, Regie
What does great writing instruction look like and sound like? How do successful teachers of writing get great writers who enjoy writing? Where do they find the time for instruction, assessment, and test prep? In Writing Essentials Regie Routman demystifies the process of teaching writing well and gives you the knowledge, research, precise instructional language, and confidence you need to succeed. With Regie's help, you'll transform your classroom into an organized, joyful writing environment where students connect reading with writing every day across the curriculum, learn essential skills like grammar and spelling, and achieve higher scores on high-stakes tests through sensible, writing-based test preparation and daily classroom-based assessment. Writing Essentials specifically and explicitly demonstrates practical, easy-to-do strategies that turn your writing instruction practices into best practices. Follow Routman's path for successfully leading all students-including English language learners, writers who struggle, and students coping with learning disabilities-from first draft to publication. You'll find expert advice and specific demonstrations on a wide variety of techniques, including: demonstrating your own writing process for students organizing and managing the writing classroom conducting effective, efficient writing conferences